EDUKASI PENINGKATAN PENGETAHUAN IBU TENTANG MP-ASI DI POSYANDU KAMPUNG SABU DESA PUKDALE (KAB KUPANG, NTT) - Brigita Dina Manek; Damita Palalangan; Diah Ayu Dwi Satiti (Universitas Mataram, 2026)
Complementary Food for Breast Milk (MP-ASI) is a food or drink containing nutrients given to infants or toddlers aged 6-12 months that are needed to meet and fulfill other than breast milk. Mothers' knowledge regarding the provision of complementary foods is still varied so that various efforts are needed to provide information with the aim of increasing mothers' knowledge in the experience of providing complementary foods, including through counseling. This activity is part of the Community Service Program in Sabu Village, Pukdale Village on December 7, 2024. The method often used is the pre-experimental design service design, namely one group pre-test post-test. The implementation of the activity went well and smoothly. Health education provided includes the definition of complementary foods, the benefits of complementary foods, the impact of deficiencies in complementary foods, guidelines for providing complementary foods, signs that a child is ready to receive complementary foods. The media used are materials in the form of powerpoints and leaflets. From the results of this community service activity, there is an increase in public knowledge, especially parents, about appropriate complementary foods for breast milk according to standards.